Immunomodulatory properties of S- and N-alkylated 5-(1H-indol-2-yl)-1, 3, 4-oxadiazole-2(3H)-thione. (February 2013) - El Ashry, El Sayed H.; El Tamany, El Sayed H.; Abd El Fattah, Mohy El Din; Aly, Mohamed R. E.; Boraei, Ahmed T. A.; Mesaik, M. Ahmed; Abdalla, Omer M.; Fatima, Beenish; Jabeen, Almas; Shukrulla, Ahmed; Soomro, Samreen
<x xml:space="preserve">Abstract</x> A series of S- and N-alkylated indolyloxadiazoles 2–7 were prepared. All compounds were tested for their immunomodulatory activity against T-cell proliferation, oxidative burst and cytokine analysis. Compounds 1, 2a, 2b, 2c and 2k demonstrated highly significant (P ≤ 0.005) inhibition on PHA activated T-cell proliferation with IC50 less than 3 µg/mL concentration, while 3b exert a moderate inhibitory effect with IC50 8.6 µg/mL. Among all compounds of the series, only 2h was found to suppress phagocytes ROS production (IC50 2.4 µg/mL) in luminol-based chemiluminescence (CL) assay. Compounds 2a-k have stimulatory effect on proinflammatory cytokine predominantly IL-1β but no effect on IL-4 and NO production indicating that these compounds might have selective inhibitory effect on T-cell proliferation. Cytotoxic effect on T-cell proliferation was tested on NIH-3T3 mouse fibroblast normal cell line. All compounds were found to be free from toxic effects up to 100 μM concentration.